Perception of Prospective Taxpayers: Tax Ethics and Tax Evasion - Ludigdo, Unti; Pusposari, Devy; Puspita, Ayu Fury (Akuntansi: Jurnal Akuntansi Integratif, 2023)
This study aimed to determine the arguments of prospective taxpayers at the Faculty of Economics and Business of Universitas Brawijaya to justify tax evasion. This study was an exploratory research with a survey approach involving 96 respondents from the Faculty of Economics and Business, Brawijaya University. The data obtained was analyzed using descriptive statistics used Statistical Package for The Social Science program. Previous research determined that the higher a person’s earnings, the lower his or her tendency to commit evasion of tax, while based on respondent percepstions this study showed that the higher someone’s income, the greater her or his probability to commit tax evasion. Related to employment, no significant distinction regarding employment and tax evasion. However, this study showed that some jobs encourage the workers to commit tax evasion. The study found obstacles in the research subjects and did not get in-depth results. Focusing attention on factors including gender, income, major, education, employment can increase the application of tax ethics and reduce the rate of tax evasion.